STUDY OF DIFFERENCES IN TIME VALUE OF MONEY WITH ECONOMIC VALUE OF TIME ON SHARIA PERSPECTIVE - Rahmayati, Rahmayati; Mardiah, Ulfa (Proceeding International Seminar of Islamic Studies, 2023)
The development of this increasingly modern era in the daily life of many Muslims doubts existing transactions. It is important to understand the difference between the time value of money and the economic value of time for Muslims so they are not trapped in ribawi transactions. In writing this journal, the method used is descriptive qualitative. The conceptual difference is that the time value of money means that money has a time value, while the economic value of time means that time has an economic value. By calculating the time value of money using a discount or interest rate while the economic value of time uses a ratio based on holding money over time. The purpose of using the time value of money is the maximum utility of the commodity while the goal of the economic value of time is the maximum maslahah in accordance with the concept of Islamic economics. According to the completeness of sharia, the time value of money is not in accordance with the sharia concept, namely the use of interest and this is included in usury, while the economic value of time is in accordance with sharia because it does not contain usury because it is time based. Therefore, it is necessary to socialize and educate the public about the difference between the Time Value of Money and the Economic Value of Time.